Avaliação da presença de microcistina-LR por HPLC-PDA em amostras de mananciais da Região da Grande Vitória - Martins, Cecília Freitas (2010)
This study aimed to evaluate the presence of MC-LR dissolved in four surface waters in the Region of Grande Vitória and effluent of sewage treatment. The HPLC-PDA method used showed satisfactory linearity (r = 0.99), recovery (62.7%) and precision (CV = 2.1%). The DL (0.17 µg.L-1) and QL (0.37 µg.L-1) were lower than the value established by WHO (1.0 µg.L-1) for drinking water, thus acceptable for the determination of MC-LR. The method was applied to environmental samples and was unable to reliably detect the presence of the toxin in samples of effluent from sewage treatment. For samples of raw water the method had average recovery factor (51.9%) and was efficient in the evaluation of MC-LR. We observed high levels of MC-LR in Jacuném Lake (4.78 µg.L-1), low concentration of toxin in Parque Pedra da Cebola Lake (0.42 µg.L-1) and MC-LR was detected in two samples of the Duas Bocas reservoir (<0.37 µg.L-1). All water bodies showed high temperature and pH conditions favorable to growth of cyanobacteria. The artificial environments, facultative pond WWTP and Parque Pedra da Cebola Lake, were classified as hypereutrophic. The Jacuném Lake was classified as supereutrophic, the Duas Bocas reservoir as mesotrophic and Juara Lake as oligotrophic. It is suggested carried out continuous monitoring of cyanotoxins in Jacuném Lake and Duas Bocas reservoir, because of their uses for fishing and recreational activities and for public supply.